Imaging Evaluation of Insertion Point Accuracy in Retrograde Intramedullary Femoral Nailing. - He, Miao; Tian, Shanshan; Liu, Jian; Deng, Xu; Xiang, Jiangxia (BioMed Research International, 2022)
Objective. When compared with visual retrograde intramedullary nail placement in the femur, fluoroscopic retrograde intramedullary nail placement in the femur improved the accuracy of insertion. Methods. Ninety-six patients treated with retrograde intramedullary nailing of the femur for femoral fracture were included in this retrospective case-control study, including 48 patients treated with nailing under direct vision and 48 patients treated with nailing under fluoroscopy. Influencing factors potentially associated with the deviation of the needle insertion point on the coronal and sagittal planes (including the needle insertion method, use of limited open reduction, side, intramedullary nail diameter, mechanism of injury, and fracture classification) were analyzed univariately; then, the variables with a p value < 0.20 on univariate analysis were included in the linear regression equation to assess the independent factors associated with needle insertion point deviation. Results. On the coronal plane, the insertion point deviation in the visual nail placement group (1.11 ± 4.08 mm) was not significantly different (p = 0.13) from that in the fluoroscopic nail placement group − 0.44 ± 3.48 mm ; on the sagittal plane, the insertion point deviation in the visual nail placement group (4.91 ± 4.67 mm) was significantly greater than that in the fluoroscopic nail placement group (2.08 ± 2.97 mm) (p < 0.01). Visual nail placement was a risk factor for insertion point deviation on the sagittal plane compared with fluoroscopic nail placement (β = − 0.84 , p < 0.01). Conclusion. Compared with visual nail placement, fluoroscopic nail placement improves the accuracy of insertion on the sagittal plane, with no difference between the two methods on the coronal plane. These findings indicate that surgeons should exercise more caution when placing nails under direct vision.